Nutraceuticals as Functional Foods - Gupta, Somya; Parvez, Nayyar; Sharma, Pramod Kumar (Journal of Nutritional Therapeutics, 2015)
Nutraceuticals are considered to be fortified or enriched foods providing all the essential nutrients required for maintaining the optimal health. A numerous studies have suggested the potential association of nutraceuticals with diet and health. This article gives a brief review on the classification of nutraceuticals on the basis of the availability of the nutraceutical from the natural sources which is further being processed and proving its medical health benefits in the market. The review also summarizes about the functional nutraceuticals acting as dietary supplements, suggested to have the capacity to significantly contribute to the modulation of the complex mechanisms of disease pathology with a view being that they may be essential in optimizing in vivo defences and help in maintaining wellness. Nonetheless, several more clinical and biological studies are needed to support guidelines for the intake of nutraceutical for the prevention and treatment in specific diseases and its medical benefits.